2015
DOI: 10.1097/bcr.0000000000000107
|View full text |Cite
|
Sign up to set email alerts
|

A 365-Day View of the Difficult Patients Treated in an Australian Adult Burn Center

Abstract: Although the effect of burns on mental health has been well examined, the aims of this study were to determine the prevalence of pre-existing mental health, drug and alcohol, and forensic problems in an Australian burn patient population; examine differences between these groups in terms of burns characteristics and healing; and also establish any patterns of presentation amongst these groups. Retrospective case notes of all the acute burn admissions, 273 patients, into a busy tertiary adults burn center in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…As in the other studies on drug and alcohol use among burn patients, we found that intoxicated patients were more likely to have a flame burn than their sober counterparts. [3, 7, 11, 12] Moreover, patients who used illicit drugs of any sort had a significantly larger burden of injury, and were also more likely to sustain an inhalation injury than those who did not use drugs. In particular, the effect on burn size seems to be due more to drugs other than marijuana, as average burn size among those who used marijuana only was quite similar to that of nondrug users at around 9-9.5% TBSA, while those who used other drugs (with or without marijuana) had burn sizes of 11.5-11.9% TBSA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As in the other studies on drug and alcohol use among burn patients, we found that intoxicated patients were more likely to have a flame burn than their sober counterparts. [3, 7, 11, 12] Moreover, patients who used illicit drugs of any sort had a significantly larger burden of injury, and were also more likely to sustain an inhalation injury than those who did not use drugs. In particular, the effect on burn size seems to be due more to drugs other than marijuana, as average burn size among those who used marijuana only was quite similar to that of nondrug users at around 9-9.5% TBSA, while those who used other drugs (with or without marijuana) had burn sizes of 11.5-11.9% TBSA.…”
Section: Discussionmentioning
confidence: 99%
“…[3] On unadjusted analysis, patients who abused any illicit drugs had longer hospital and intensive care unit stays, but not a higher risk of mortality. After stratifying based on the pattern of drug use, marijuana alone does not appear to worsen outcomes, while use of other drugs seem to result in the longest hospitalization and highest risk of death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] As physical treatments have improved survival, attention has increasingly turned to psychosocial outcomes with a growing call for psychosocial screening, psychosocial support and treatment of psychiatric sequelae such as posttraumatic stress disorder (PTSD), depression, anxiety and substance use. [4][5][6][7][8] In parallel, research, both qualitative and quantitative, has examined risk factors for poorer coping and changes to body image and protective factors that foster resilience, recovery and posttraumatic growth. [2][3][4][5][6][7][8][9][10][11][12][13] Furthermore, injuries do not occur in a vacuum; many patients have prior mental health issues, complex trauma, substance use or forensic issues that can complicate their treatment and progress.…”
mentioning
confidence: 99%